Les réseaux sociaux numériques : des discours de promotion à la déﬁnition d’un objet et d’une méthodologie de recherche - Stenger, Thomas; Coutant, Alexandre (HERMES - Journal of Language and Communication in Business, 2010)
The increase in popularity and number of users of social networks sites such as Facebook, Hi5 or MySpace has raised numerous questions. Companies are debating the commercial opportunities and questioning the promotional messages of these sites. Researchers, particularly those in human and social sciences, are facing a lack of clear deﬁnition for this new topic, which is often confused with other so-called “social media”. The tendency to re-circulate classic marketing theory without questioning its relevance must be avoided, as well as the tendency to confuse potential and effective uses, and the lack of objectivity which prevents a comprehensive understanding of the complex process involved in marrying the technical characteristics of the facility to the creative skills of the users. This article aims to tackle these questions and, in so doing, deﬁne social network sites more precisely as well as propose a methodology focused on the uses and daily practices of internet users.